Improving Photoelectrochemical Activity of Magnetron-Sputtered Double-Layer Tungsten Trioxide Photoanodes by Irradiation with Intense Pulsed Ion Beams - Alshyn Abduvalov; Marat Kaikanov; Timur Sh. Atabaev; Alexander Tikhonov (Nanomaterials, 2022)
The photoelectrochemical (PEC) activity of metal oxide photoelectrodes for water-splitting applications can be boosted in several different ways. In this study, we showed that PEC activity can be significantly improved with a double-layer (crystalline-amorphous) configuration of WO3 thin films irradiated with intense pulsed ion beams (IPIB) of a nanosecond duration. It was found that IPIB irradiation promotes the formation of crystalline and sponge-like WO3 structures on the surface. Due to an increase in the active surface and light scattering in irradiated samples, photocurrent generation increased by ~80% at 1.23 reversible hydrogen electrodes (RHE).